2019
DOI: 10.1017/s0033291718003823
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and adult suicidality: a comprehensive systematic review with meta-analysis

Abstract: This comprehensive systematic review and meta-analysis aims to quantify the association between different types of childhood maltreatment and suicidality. We searched five bibliographic databases, including Medline, PsychINFO, Embase, Web of Science and CINAHL, until January 2018. Random-effects meta-analysis was employed followed by univariable and multivariable meta-regressions. Heterogeneity was quantified using theI2statistic and formal publication bias tests were undertaken. The methodological quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
181
3
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 275 publications
(233 citation statements)
references
References 100 publications
28
181
3
6
Order By: Relevance
“…This study had four main strengths with two key clinical implications. First, considering the high rates of the OCD symptoms in the community and in view of recent evidence suggesting that individuals who are not under the care of clinicians are at higher risk for engagement in suicidal ideation and behaviors (Angelakis et al, ), we focused primarily on people from the extant community in an effort to encourage the development of efficient community‐based interventions (for a detailed overview of the advances of the community‐based research, see Israel, Schulz, Parker, & Becker, ). Second, we incorporated a large representative community sample that was balanced in terms of demographic information including age, gender, occupation, and socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…This study had four main strengths with two key clinical implications. First, considering the high rates of the OCD symptoms in the community and in view of recent evidence suggesting that individuals who are not under the care of clinicians are at higher risk for engagement in suicidal ideation and behaviors (Angelakis et al, ), we focused primarily on people from the extant community in an effort to encourage the development of efficient community‐based interventions (for a detailed overview of the advances of the community‐based research, see Israel, Schulz, Parker, & Becker, ). Second, we incorporated a large representative community sample that was balanced in terms of demographic information including age, gender, occupation, and socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent reviews by Carr, Duff, and Craddock (, ) similarly found that CSA survivors were at a higher risk of a range of psychosocial, physical and mental health difficulties. Systemic reviews have also specifically established that CSA is a risk factor for depression, anxiety, Post Traumatic Stress Disorder (PTSD) (Amado, Arce, & Herraiz, ; Hillberg, Hamilton‐Giachritsis, & Dixon, ); sexual exploitation (De Vries & Goggin, ), intimate partner violence (Li, Zhao, & Yu, ), suicidality (Angelakis, Gillespie & Panagioti, ), substance abuse (Halpern et al, ), and educational difficulties (Fry et al, ). Reviews have also demonstrated a range of psychosocial protective factors that can help reduce risk, including family and social supports, personal attributes, active coping style, a sense of personal influence, and externalising blame for the abuse (Carr, Duff, & Craddock, , ).…”
Section: Introductionmentioning
confidence: 99%
“…An important issue to be investigated in future studies would be widening the dimensions of parenting to include not only care and overprotection, but also abuse and childhood maltreatment. Findings from a recent meta‐analysis (Angelakis, Gillespie, & Panagioti, ) indicate that all types of childhood abuse are associated with increased risk for suicidal ideation and suicide attempts in adults independent of demographic, clinical, and methodological variations across the studies. The authors of the meta‐analysis suggest that the literature is still lacking in respect of empirical evidence for the mechanisms by which experiences of childhood maltreatment exert their detrimental and long‐lasting impact on suicide risk.…”
Section: Discussionmentioning
confidence: 99%
“…Its items are rated on a 5-point scale (from 1 = "Not at all like me" to 5 = "Very much like me") (e.g., "I find it difficult to depend on other people" and "I am comfortable having other people depend on me"). This measure has been used to assess different models/dimensions of adult attachment (Andersen et al, 2017;Roisman et al, 2007). For the present study (N = 717), we assessed dimensions of attachment anxiety (x = 0.859, SE = 0.008, CI = 0.842-0.876) and attachment avoidance (x = 0.813, SE = 0.011, CI = 0.791-0.836).…”
Section: Adult Attachment the Relationshipmentioning
confidence: 99%
See 1 more Smart Citation